Hubungan Pengetahuan, Sikap dan Pola Penggunaan Earphone dengan Kejadian Tinnitus pada Siswa SMA Negeri 7 Kota Kupang - Freitas, Apendita Joice; Christiani Berek, Noorce; Romeo, Petrus (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2022)
The development of telecom and audio-visual technology has increased rapidly with the discovery of various portable devices, one of which is earphones. The problem is that improper use of earphones can cause various hearing problems, one of which is tinnitus. The initial study conducted foud than out of 10 students interviewed, 9 of them experienced tinnitus. The aims of the study is to aware the correlations of knowledge, attitude and earphone usage pattern with tinnitus incidence on SMA Negeri 7 Kupang City students. This is a quantitative study with approach by cross-sectional. There is 75studens total sample which selected with consecutive technique sample. Each of the variables was studied with the Chi Square test to determine the relationship with the tinnitus incidence variable. The results of the statistical test showed the relationship of knowledge of earphone use with the incidence of tinnitus p = 0.004 (< 0.05), the p value of the earphone usage attitude variable with the tinnitus incidence variable is known to be p=0,015 (<0,05), and the relationship of earphone use patterns with the incidence of tinnitus p = 0.000 (<0.05). In conclusion, there is a relationship between knowledge, attitudes and earphone usage pattern with tinnitus incidence on students of SMAN 7 Kupang City.